2000
DOI: 10.1002/1521-3773(20000616)39:12<2120::aid-anie2120>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Based NO Sensing by Selective Ligand Dissociation

Abstract: Nitric oxide reacts selectively with the O2 stable, weakly fluorescent complex [Co(DATI‐4)] in dichloromethane solution to dissociate a fluorophore‐substituted arm of the aminotroponiminate ligand DATI‐4. The resulting cobalt–dinitrosyl adduct (see picture) effects a positive fluorescence response. The detection limit of 2 is 50–100 μM for NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 12 publications
(18 reference statements)
2
61
0
Order By: Relevance
“…This general approach relies on quenching of pendant fluorophores by coordination to a paramagnetic and/or heavy-metal centre, where NO can selectively displace and release the fluorophore by metal–ligand substitution with a concomitant emission turn-on response. This strategy has been applied to a broad spectrum of coordination chemistry motifs; examples include iron cyclam 64 , cobalt aminotroponimine 65 , ruthenium porphyrin 63 and dirhodium tetracarboxylate 66 platforms.…”
Section: Metal-mediated Reaction-based Fluorescent Probesmentioning
confidence: 99%
“…This general approach relies on quenching of pendant fluorophores by coordination to a paramagnetic and/or heavy-metal centre, where NO can selectively displace and release the fluorophore by metal–ligand substitution with a concomitant emission turn-on response. This strategy has been applied to a broad spectrum of coordination chemistry motifs; examples include iron cyclam 64 , cobalt aminotroponimine 65 , ruthenium porphyrin 63 and dirhodium tetracarboxylate 66 platforms.…”
Section: Metal-mediated Reaction-based Fluorescent Probesmentioning
confidence: 99%
“…While there appears to be no recent work reported, the example of Lippard is included for completeness (Scheme 5). 14 In 2009, Strano and coworkers demonstrated that a diaminophenyl-functionalised dextran polymer enables the rapid and direct response of single-wall nanotubes (SWNTs) to nitric oxide. 15 Since this "early" discovery, this group went on to prepare fluorescent SWNT-based sensors comprised of singlestranded d(AT)15 DNA oligonucleotide-encased nanotubes (AT15-SWNT).…”
Section: Detection Of Nitric Oxidementioning
confidence: 99%
“…For some time, there has been an interest in possible utilization of the NO reduction of coordinated metal complexes of luminescent ligands as turn-on sensors for NO detection [142,143]. In this context, it is of interest that in weakly coordinating solvents, the cuprous complex Cu(dmp) 2 + is strongly luminescent from its metal-to-ligand charge transfer (MLCT) state(s), while the Cu(II) analog is not [144].…”
Section: +mentioning
confidence: 99%